The Existence of the Betel Lime Business on Sugara Island - Syahrul Ramadhan; Ersis Warmansyah Abbas; Sovia Husni Rahmi; Rusmaniah Rusmaniah; Raihanah Sari (The Innovation of Social Studies Journal, 2025)
Research objective: Describe the existence of the Betel Lime Production Business in Sugara Island Village. The approach used in this research is qualitative with historical methods. Data collection was carried out by observation, interviews and documentation. The research subjects were the village head, chairman of the betel lime business group, betel lime entrepreneur. There are research instruments including interview guides and recording equipment and writing instruments. Data were analyzed using data reduction techniques, data presentation and drawing conclusions. Validity testing is carried out through extended observations, increased persistence and triangulation. Research Results: The existence of the Betel Lime Production Business on Sugara Island to this day still exists to maintain the traditions that exist in the family of betel lime entrepreneurs. The diversity of the whiting business has also become one of the means of improving the community's economy and developing tourism in the tradition of whiting production which is currently rare. Implementing the whiting production business itself includes preparing raw materials, burning, mixing and storing or packaging and marketing. The conclusion of this research is that the results provide an explanation that the existence of the whiting production business on Sugara Island has become part of the history and traditions of the Sugara Island village. The existence of the Betel Lime Production Business on Sugara Island has become the only center for making Betel Lime in South Kalimantan. The existence of this production business also provides the uniqueness of superior products in Sugara Island Village. This business also provides employment opportunities for the people in the village. The importance of maintaining family traditions for some of the people there has made the Betel Lime Business on Sugara Island continue to survive to this day.